2019
DOI: 10.1016/j.jfda.2018.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Revisit gut microbiota and its impact on human health and disease

Abstract: Trillions of microbes have evolved with and continue to live on human beings. With the rapid advances in tools and technology in recent years, new knowledge and insight in cross-talk between the microbes and their hosts have gained. It is the aim of this work to critically review and summarize recent literature reports on the role of microbiota and mechanisms involved in the progress and development of major human diseases, which include obesity, hypertension, cardiovascular disease, diabetes, cancer, Inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
123
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(133 citation statements)
references
References 95 publications
1
123
0
2
Order By: Relevance
“…The intestinal microbiota plays a crucial role in the maintenance of host homeostasis by shaping and supporting multiple physiological functions, such as nutrient absorption, metabolism, and the development of the immune system (Ding et al, 2019;Richard and Sokol, 2019;Sonnenburg and Sonnenburg, 2019;Sovran et al, 2019;Zmora et al, 2019). The microbiota also outcompetes intestinal colonization by microbial pathogens and thus provides an exogenous defense mechanism against infections (Rodriguez et al, 2015;Stecher and Hardt, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal microbiota plays a crucial role in the maintenance of host homeostasis by shaping and supporting multiple physiological functions, such as nutrient absorption, metabolism, and the development of the immune system (Ding et al, 2019;Richard and Sokol, 2019;Sonnenburg and Sonnenburg, 2019;Sovran et al, 2019;Zmora et al, 2019). The microbiota also outcompetes intestinal colonization by microbial pathogens and thus provides an exogenous defense mechanism against infections (Rodriguez et al, 2015;Stecher and Hardt, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These modifications (gain or loss of community members or changes in their relative abundance), termed dysbiosis, can impact the metabolic activity of the microbiota, with consequences on its mutualistic relationship with the host. Indeed, microbiota dysbiosis is associated with the pathogenesis of age-related diseases, including metabolic diseases, as well as cancers, neurodegenerative and psychiatric disorders (Alvarez-Mercado et al, 2019;Ding et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Innumerable studies indicated that changes in the composition of the gut microbiota were related to the development of various diseases including obesity. 18 Lesser diversity and richness, increased ratio of the major phyla Firmicutes/Bacteroidetes and changes in several bacterial species are common features of both obesity mice and human fecal samples. 10 Moreover, obese animals with gut dysbiosis often have impaired intestinal integrity.…”
Section: Discussionmentioning
confidence: 99%